Mapping knowledge structure and emerging trends of extracorporeal membrane oxygenation for acute respiratory distress syndrome: a bibliometric and visualized study - Lu, Yanqiu; Li, Wanqing; Qi, Shaoyan; Cheng, Kunming; Wu, Haiyang (Frontiers in Medicine, 2024)
Introduction With the discovery of extracorporeal membrane oxygenation (ECMO), it is considered as a valuable tool for supporting the treatment of severe acute respiratory distress syndrome (ARDS). It has gained increasing attention, particularly during the COVID-19 epidemic. However, to date, no relevant bibliometric research on the association between ECMO and ARDS (ECMO-ARDS) has been reported. Our study aimed to summarize the knowledge structure and research focus of ECMO-ARDS through a bibliometric analysis. Method Publications related to ECMO-ARDS from 2000 to 2022 were obtained from the Web of Science Core Collection (WoSCC). Research data underwent bibliometric and visual analysis by using CiteSpace, VOSviewer, and one online analysis platform. By analyzing the countries, institutions, journals, authors, the geographic distribution of research contributions as well as the leading institutions and researchers in this field were identified. Additionally, prominent journals and highly cited publications were highlighted, indicating their influence and significance in the field. Moreover, the co-citation references and co-occurring keywords provided valuable information on the major research topics, trends, and potential emerging frontiers. Results A total of 1,565 publications from 60 countries/regions were retrieved. The annual publication number over time revealed exponential growth trends (R2 = 0.9511). The United States was dominant in ECMO-ARDS research, whereas the Univ Toronto was most productive institution. Prof Combes A published the most publications in this area. ASAIO Journal and Intensive Care Medicine were the most active and co-cited journals, respectively. Reference co-citation analysis showed that current research focus has shifted to COVID-related ARDS, multi-center studies, as well as prone positioning. Apart from the keywords “ECMO” and “ARDS”, other keywords appearing at high frequency in the research field were “COVID-19”, “mechanical ventilation”, “extracorporeal life support”, “respiratory failure”, “veno-venous ECMO”, “SARS-CoV-2”, “outcome”. Among them, keywords like “mortality”, “veno-venous ECMO”, “epidemiology”, “obesity”, “coagulopathy”, “lung ultrasound”, “inhalation injury”, “noninvasive ventilation”, “diagnosis”, “heparin”, “cytokine storm” has received growing interest in current research and also has the potential to continue to become research hotspots in the near future. Conclusion This bibliometric analysis offers a comprehensive understanding of the current state of ECMO-ARDS research and can serve as a valuable resource for researchers, policymakers, and stakeholders in exploring future research directions and fostering collaborations in this critical field.